Digital Control Systems Lecture Notes PDF
Document Details
Uploaded by Deleted User
University of M'hamed Bougara of Boumerdes
Prof. R. BOUSHAKI
Tags
Summary
These lecture notes cover digital control systems, including different design methods like the backward and forward difference methods, and the matched pole-zero mapping method. The document emphasizes the transition from analog to digital control systems.
Full Transcript
# University of M’hamed BOUGARA of Boumerdes ## Institute of Electrical and Electronic Engineering ### Lecture EE451/Master 1 ## DIGITAL CONTROL SYSTEMS ### Prof. R. BOUSHAKI ## Chapter 3: Design of Discrete-Time Control Systems ### 3.1 Introduction: We will study different methods in order to find...
# University of M’hamed BOUGARA of Boumerdes ## Institute of Electrical and Electronic Engineering ### Lecture EE451/Master 1 ## DIGITAL CONTROL SYSTEMS ### Prof. R. BOUSHAKI ## Chapter 3: Design of Discrete-Time Control Systems ### 3.1 Introduction: We will study different methods in order to find discrete equivalent of analog controllers or filters. Using the following circuit: A circuit diagram consisting of a resistor, a capacitor, an input signal, and an output signal. The transfer function of this circuit has the form: $ \frac{y(s)}{x(s)} = \frac{a}{s+a} $ $ \Rightarrow ax(s) = sy(s)+ay(s) = ax(t) = \frac{dy(t)}{dt} +ay(t) $ We need to derive difference equation whose solution will approximate the solution of the differential equation, and then, we will get the equivalent discrete time filter (controller). ### 3.2 The backward difference method: Let's have: $ \frac{dy}{dt} =-ay+ ax $ Calculate the integral for t : (k-1)T <t≤kT $ \int_{(k-1)T}^{kT} \frac{dy}{dt} dt = -a \int_{(k-1)T}^{kT} y(t)dt+a \int_{(k-1)T}^{kT} x(t)dt $ $ y(kT)-y((k-1)T)=-a \int_{(k-1)T}^{kT} y(t)dt+a \int_{(k-1)T}^{kT} x(t)dt $ We will approximate the areas by taking: $ \int_{(k-1)T}^{kT} y(t)dt = y(kT).T (Backward: t=kT) $ And $ \int_{(k-1)T}^{kT} x(t)dt = x(kT).T $ A graph showing the backward method of integration. $ -1 So: y(kT) = y((k-1)T)-aT[y(kT)+x(kT)] \Rightarrow y(z)=z¯¹y(z)-aT[y(z)+x(z)] $ $ \frac{Y(z)}{X(z)} = G(z) = \frac{ -1 aT + aT a }{ 1- z¯¹ + aT } = \frac{ a }{ 1-z¯¹ + a } $ $ \frac{Y(z)}{X(z)} = \frac{a}{s+a} with: s = \frac { z -1 }{Tz} $ Mapping from S-plane to Z-plane Remark: Let's get interested into the stability region in the Z-plane using the mapping. A graph comparing the S-plane and Z-plane transformation. $ From : Re(S) <0>Re(\frac { 1 -z^{-1} }{T} )<0 ⇒ Re(\frac { z^{-1} }{T} )>0 From: Re(\frac { z^{-1} }{Tz} )<0 $ $ With: z=σ+jw So: Re(\frac { z^{-1} }{Tz} ) = Re[ \frac { σ +jw−1 }{T(σ+jw)} ]<0 $ $ \Rightarrow Re[( σ+jw−1)( σ-jw)]<0 ⇒σ²-σ+w²£0 $ $ \Rightarrow(σ-1/2)^2 +w²-1/4 <0 $ Circle: The center σ = 1/2; w = 0 ; Radius =1/2 ### 3.3 The forward difference method: $ \int_{(k-1)T}^{kT} y(t)dt = y((k-1)T).T (Forward: t=(k-1)T) $ $ \int_{(k-1)T}^{kT} x(t)dt = x((k-1)T).T $ A graph illustrating the forward method of integration. From: y(kT) = y[(k-1)T]-aT.[y((k-1)T]+x((k-1)T) $ \Rightarrow y(kT)=(1-aT)y[(k-1)T]+aT.x((k-1)T) $ $ \Rightarrow y(z) = (1-aT)z^*y(z)+aT.z¹.x(z) \Rightarrow G₁(z) = \frac {y(z)}{x(z)} = \frac {a}{1-z¯¹ + a } $ $ \frac{Y(z)}{X(z)} = \frac{a}{s+a} with:s = \frac { 1 -z^{-1} }{Tz-1 } = \frac {z-1}{T(z-1)} $ Mapping from S-plane to Z-plane Remark: Stability means Re(s) <0⇒ Re[ Z−1 / T ]<0⇒ Re(z) <1 Conclusion: Backward: t = kT $ S=\frac{z -1}{Tz} $ Forward: t = (k-1)T $ s = \frac {z -1}{T} $ A graph with the unit circle with the stability region shaded. ### 3.5 The matched pole-zero mapping method: We follow the given procedure: 1) The transfer function G(s) should be in a factored form. The poles (or zeros) of G(s) are mapped into the Z-plane using : - For finite poles and zeros: z = e^st - For infinite poles and zeros: z = -1 A graph depicting the mapping from the S-plane to the Z-plane. Remark: Adjust the gain of the discrete time function G₁(z) in order to match the gain of the continuous time G(s). Example: Find the discrete PTF: GD (z)? Adjust the gain K for low pass case. $ G(s) = \frac{a}{s+a} \Rightarrow \begin{cases} infinite zero \rightarrow z = -1 \\ finite pole: s = -a \rightarrow z = e^{sT} \Rightarrow z =e^{-aT} \end{cases} $ Solution: $ G_D(z) = K \frac {z + 1 }{ (z - e^{-aT} )} \Rightarrow \begin{cases} infinite zero: z = -1 \\ finite poles: z = e^{-aT} \end{cases} $ for s = 0 ⇒ z = 1 So G_D(1) = Let's adjust K: from z = e^{st} ; we have: When s → 0 then z→ 1 So G_D(1) = G(0) $ \Rightarrow \begin{cases} G_D(1) = G_D(z)|_{z=1} = \frac{2K}{(1-e^{-aT})}\\ G(0) = \frac{a}{s+a} |_{s=0}=1 \end{cases} \Rightarrow \frac{2K}{1-e^{-aT}} = 1 \Rightarrow K = \frac{1-e^{-aT}}{2} $ $ \Rightarrow G_D(z)=(\frac {1-e^{-aT}}{2})*(\frac {z+1}{z-e^{-aT}}) $ Examples: 1) G(s) = (s + b)/(s + a) 2) G(s) = s/(s + a) $ Find G_D(z)? \begin{cases} finite pole: s = -a \rightarrow z =e^{sT} \Rightarrow z = e^{-aT} \\ infinite zero: s \rightarrow +∞ \rightarrow z = -1 \end{cases} $ 1) G(s) = (s + b)/(s + a) →Gp(z) = K(z-e^{-bT})/(z-e^{-aT}) When s → 0 then z→ 1 $ G_D(1) = G(0) \Rightarrow K(\frac {1-e^{-bT}}{1-e^{-aT}}) = \frac{b}{a} \Rightarrow K = \frac{b}{a}(\frac {1-e^{-aT}}{1-e^{-bT}}) $ 2) G(s) = s/(s + a) → G_D(z) = K(z-1)/(z-e^{-aT}) Remark: For G_D(1) = G(0) we get K=0 (it is not required) When s → -∞ then z→ -1 $ G_D(-1) = G(-∞) \Rightarrow K(\frac {-2}{1-e^{-aT}})=-1 \Rightarrow K = \frac {1+e^{-aT}}{2} $ ### 3.5.1 Step Invariance method: G_D(z) has the same step response as G(s) at the sampling instants. $ G_D(z) = (1-z^{-1})Z^{-1}[\frac {1}{s}L^{-1}(G(s))] = (1-z^{-1})Z^{-1}[\frac {G(s)}{s}] $ ### 3.5.2 Impulse Invariance method: The impulse response of G_D(z) is T times the impulse response of G(s) at t=kT With: g_D(kT) = Z^{-1}[G_D(z)] is the impulse response of G_D(z) And: g(t) = L^{-1}[G(s)] is the impulse response of G(s) $ \Rightarrow g_D(kT)=T.g(t) \Rightarrow g_D(kT) = Tg(t) \Rightarrow G_D(z) = Z[g_D(kT)] = T.Z(g(t)) $ $ G_D(z) = T.G(z) With: G(z) = Z[G(s)] $ ### 3.6 Root Locus in Z-plane: The root locus of an (open-loop) transfer function G(s) is a plot of the locations (locus) of all possible closed-loop poles with proportional gain K. A block diagram of a closed loop system. Closed-loop poles are the solutions to the characteristic equation: 1+ K.GH(z) = 0 $ GH(z) = \frac { (z-z_1)(z - z_2).....(z- z_m) }{ (z - P_1)(z - P_2 ).....(z-P_n) } $ with m open-loop zeros z1, ...,zm and n open-loop poles p1, ...,pn (m≤n) How do the “n” closed-loop poles change as K varies from 0 to ∞? ### 3.6.1 Root Locus Overview - The root locus of a characteristic equation: $ 1+K \frac { (z-z_1)(z - z_2.)....(z- z_m) }{ (z - P_1)(z - P_2 ).....(z-P_n) } = 0 $ consists of n branches - Start from the n open-loop poles p1,..., pn at K=0 - m of them converge to the m open loop zeros z1,...,Zm - The other (n-m) diverge to ∞ along of the center of asymptotes: σ = ( Σ_{i=1}^n P_i - Σ_{i=1}^m z_i)/(n-m) with angles: θ = (2l+1)180°/(n-m) = ±90°,±270°,...with: 1=1,....,n-m Examples: A graph depicting the root locus of a system when n-m=0,1,2,3. n-m=2, the branches start at the poles and go to infinity. ### 3.6.2 Phase Angle Condition An arbitrary point z is on the root locus if and only if: $ [∠(z-z₁)+...∠(z−z_m)]-[∠(z-p₁)+...∠(z-p_n)] = (2l+1)180° $ Example: A graph displaying the angles of the root locus. z is on the root locus if and only if: for some integer 1 $ (φ + φ_2) - (θ_1 + θ_2) = (2l+1)180° $ ### 3.6.3 Magnitude Condition: For a point z that is known to be on the root locus, we can find the corresponding K: $ Form: 1+ K \frac { (z - z₁ ) (z - z_2 ).....(z- z_m ) }{ (z - p₁)(z - p_2 ).....(z-p_n) } = 0 \Rightarrow K = _ \frac { (z - p₁)...(z - p_n) }{ (z - z₁)...(z - z_m) } \Rightarrow K = \frac { z - p_1..z-p_n }{ z - z_1..z - z_m } $ A graph displaying the various angles. Characteristic equation: 1 + K(B(z)/A(z)) = 1 + K( (z -z_1)...(z-z_m) )/( (z-p_1)...(z-p_n) ) = 0 ### 3.6.4 Breakin/Breakaway Points σ_b Breakaway points (points of departure from the real axis) correspond to local maxima of K, whereas break-in points (points of arrival at the real axis) correspond to local minima of K. In order to find σ_b we solve 1+K(B(z)/A(z)) = 0,so K= -A(z)/B(z) Break in/Break away (σ_b) points are the solutions of dK/dz = 0 - The angle of departure from a complex pole p_n is given by: 180° – Σ_{i=1}^{n-1} ∠(p_n - p_i) + Σ_{j=1}^m ∠(p_n - z_j) Example: A closed loop system with a transfer function: G(s) = (1-e^-Ts)/s. 1)Solving the characteristic equation for K: $ 1+ K \frac { 0.368z+0.264 }{z^2 -1.368z+0.368} = 1 + K \frac { 0.368(z+0.7174) }{ (z-1)(z-0.368) } = 0 $ Calculate the: dK/dz = 0 and solve the equation for z to find (Breakin/Breakaway points). The Open-loop zeros and poles: $ K = -\frac {(z−1)(z-0.368)}{0.368(z+0.7174)} \Rightarrow \frac { dK }{dz} = \frac {d}{dz}( \frac {(z−1)(z-0.368)}{0.368(z+0.7174) }) = 0 $ The solutions for z (Breakin/Breakaway points) are: z = 0.65(so then K = 0.196) z = −2.08(sothen K =15) ### 3.6.5 Points, where the root cross the Unit Circle - This is the case when the closed-loop system changes from being stable to being unstable (or vice versa): - Correspond to marginal stability and can be found by - Root locus graphically - Routh-Hurwitz criterion - Jury Test How to Determine K using Routh-Hurwitz Criterion A block diagram of a closed loop system. G(z): is open loop Pulse Transfer (FTF) Characteristic equation: $ 1+G(z)=0⇒1+K \frac { 0.368(z+0.7174) }{ (z-1)(z-0.368) } = 0 $ Using the bilinear transformation: z = (1+(T/2)w)/(1-(T/2)w) and we have T=1s, then: $ ⇒(1-0.0381K)w²+(0.924-0.386K)w+0.924K = 0 $ Routh Hurwitz Table | w^2 | 1 - 0.0381K | 0.924K | |-----|------------------------|---------| | w^1 | 0.924 - 0.386K | | | w^0 | 0.924K | | Condition of stability (no change of sign) so: 1-0.0381K > 0 0.924-0.386K > 0 0.924K > 0 So the range of K for stability is: 0<K <2.39 Example: A block diagram of a closed loop system. We have G_12(z) = K/(1-z¯¹) = K(z-1)/(z-1) Draw the root locus: For t=0.5s $ G_p(z) = Z[Z.O.H \frac {1}{s+1}] = (1-z^{-1})Z[\frac{1}{s(s+1)}] $ $ =(1-z^{-1})Z[\frac {1}{s} - \frac{1}{s+1}] = (1 - z^{-1}) [\frac{z}{z-1} - \frac {z - e^{-T}}{z-1}] = \frac {1-e^{-T}}{z-e^{-T}} $ The forward PTF is (open loop) G_p(z) = (1-e^{-T})/(z-e^{-T}) $ G(z) = G_1(z).G_p(z) \Rightarrow G(z) = K \frac {(z-1)}{z-1} \frac{1-e^{-T}}{z-e^{-T}} = K \frac{1-e^{-T}}{z-e^{-T}} $ The characteristic equation is: 1+G(z) = 0 $ \Rightarrow 1+ \frac{K.z.(1-e^{-T})}{(z-1)(z-e^{-T})} =0 $ $ T = 0.5s \Rightarrow e^{-0.5} = 0.666 So: G(z) = \frac{0.393.K.z}{(z−1)(z−0.666)} $ We have: A graphical representation of the root locus of the system. $ 1+G(z) = 0 \Rightarrow K = \frac { (z−1)(z−0.666) }{0.393z} $ $ \frac {dK}{dz} = 0 \Rightarrow z^2 = 0.606 \Rightarrow σ_1,2 = ±√0.606 = ±0.778 $ For_σ_1 = 0.778⇒ K = 0.081 and For σ_2 = -0.778⇒ K =8.398 ### 3.7 Transit response Recall: $ Using: C(s) = \frac{w_n^2}{s^2 + 2ζw_ns + w_n^2} \times R(s) $ $ With: R(s) = \frac{1}{s}, step input. $ ζ :Damping factor; ω_n: Natural radian frequency; For 0< ζ <1> Under damping response. $ 1+√1-ζ^2 $ The roots are complex: S1,2 =-ζwn±jwn√1-ζ^2 $ c(t)=1-\frac {e^{-ζw_nt}}{√1-ζ^2} sin(w_n√1-ζ^2 t + a) $ with: sin(a) = √1-ζ^2 A graph showing the underdamped response of the system. We have: tp = π / (wn√1-ζ^2) Rise time: tr = 2.5/wn Delay time: td Settling time: ts ≈ 4/ζwn Damped natural frequency: ω_d = ω_n√1-ζ^2 $ We have: sin(a) = √1-ζ^2 So C(t)=1-\frac {e^{-ζw_nt}}{√1-ζ^2} sin(w_n√1-ζ^2 t + a) $ Discrete time case We will use the mapping between the S and Z planes. Example: Po ≤ 20% ; Po =100× (peak value of C(t)−1)/(step size) ; step size= 1 ts ≤20s tr≤8s $ P_0 = e^{-\zeta π/√1-ζ^2} ≤ 0.2 \Rightarrow ζ ≥ 0.5 $ $ t_s ≈ 4/σ ≈ 20 \Rightarrow σ ≈ 4/20 = 0.2 $ $ τ = t_r / w_n ≈ 8 \Rightarrow w_n ≈ 0.3125 $ A block diagram of the system. ### 3.8 Steady state errors: We now examine the effect of sampling on the steady state error. Consider the digital system given below: A block diagram of a sampled-data system with a zero-order hold block. From the figure, we have: E(z) = R(z)-HC(z) E(z) = R(z)-HG(z)E(z) $ \Rightarrow E(z) = \frac{R(z)}{1+GH(z)} $ $ With: GH(z)=(1-z^{-1})Z^{-1}[\frac {G_p(s)H(s)}{s}] $ Using the final value theorem, we find the steady state error: $ e_{ss}^* = e^*(∞) = lim_{t \rightarrow ∞} e^*(t) = lim_{k \rightarrow ∞ } e(kT) = lim_{z \rightarrow 1} (1-z^{-1})E(z) = lim_{z \rightarrow 1} (1-z^{-1}).[ \frac{R(z)}{1+GH(z)}] $ $ e_{ss}^* = lim_{z \rightarrow 1} (1-z^{-1}). [\frac{R(z)}{1+GH(z)}] $ ### 3.8.1 Position error: The Input is Unit Step: R(z) = z/(z - 1) Thus, the steady state error is: $ e_{ss}^* = lim_{z \rightarrow 1} (1-z^{-1}) [ \frac{z/(z-1)}{1+GH(z)} ] = lim_{z \rightarrow 1}[ \frac{1}{1+GH(z)} ] $ $ Defining: K_p = lim_{z \rightarrow 1} GH(z) \Rightarrow e_{ss}^* = \frac {1}{1+K_p} $ Static position error Remark: $ e_{ss}^* \rightarrow 0 \Rightarrow K_p \rightarrow ∞, we should have at least one pole at z=1 for GH(z) $ ### 3.8.2 Velocity error: The Input is Unit Ramp R(z) = Tz/(z-1)^2 ⇒ R(z) = (Tz^{-1})/(1-z^{-1})^2 The steady state error for this case is: e_{ss} = e(∞) $ \Rightarrow e_{ss}^* = e^*(∞) = lim_{z \rightarrow 1} (1-z^{-1}).[\frac{(Tz^{-1})/(1-z^{-1})^2}{1+GH(z)}] $ $ \Rightarrow e_{ss}^* = lim_{z \rightarrow 1} \frac { (1-z^{-1}) }{ (1-z^{-1})^2 } [\frac{Tz^{-1}}{1+GH(z)} ] $ $ Defining: K_v = \frac {1}{T} lim_{z \rightarrow 1}(1-z^{-1})^2GH(z): Velocity error const $ $ \Rightarrow e_{ss}^* = \frac {1}{K_v} $ Remark: $ e_{ss}^* \rightarrow 0 \Rightarrow K_v \rightarrow ∞ \Rightarrow GH(z) Should have at least 2 poles at z=1. $ ### 3.8.3 Acceleration error: The Input is Unit Parabolic : R(z) = T^2 z(z+1)/2 (z-1)^3 If we take : r(t) = t^2/2 u(t) ⇒ R(z)= (T^2 (1+z^{-1})z^{-1})/ (2(1-z^{-1})^3) ) The steady state error for this case is: e_{ss} = e(∞) $ \Rightarrow e_{ss}^* = lim_{z \rightarrow 1} (1-z^{-1}). [ \frac {T^2 (1+z^{-1})z^{-1} / (2(1-z^{-1})^3)}{1+GH(z)} ] $ $ \Rightarrow e_{ss}^* = lim_{z \rightarrow 1} [ \frac{T^2}{(1-z^{-1})^2} \frac{1}{1+GH(z)} ] $ Defining K_a : the acceleration error constant ⇒ K_a = \frac {1} {T^2} lim_{z \rightarrow 1} (1-z^{-1})^2GH(z) $ \Rightarrow e_{ss}^* = \frac {1}{K_a} $ Remark: $ e_{ss}^* \rightarrow 0 \Rightarrow K_a \rightarrow ∞ \Rightarrow GH(z) Should have at least 3 poles at z=1. $ ⇒ System type “n” is the system type: GH(z) = \frac {1}{(z-1)^n} \frac {A(z)}{B(z)} ### 3.9 The dead beat response: In the control theory, the dead-beat control problem consists of finding what input signal must be applied to a system in order to bring the output to the steady state quickly. The system response that reaches the desired value as quickly as possible is called minimum control system. Example: A block diagram showcasing the dead beat response of a system. Take: G_1(s) = 10/( (s+1)(s+2) ;T = 0.1s; $ G_{ZOH}.G_1(z) = (1-z^{-1})Z[\frac{10}{s(s+1)(s+2)}] \Rightarrow G_p(z) = \frac{0.0453(z−1)(z +0.904)}{(z - 0.405)(z – 0.819)} $ Suppose now that: G_2(z) = (z – 0.405)(z -0.819)/(0.0453(z−1)(z +0.904)) $ Using pole zero cancellation: G(z).G_{ZOH}.G_1(z) = 1 $ Let's now: R(z) = 1/(1-z¯¹) = (z-1)/(z-1) =(unitstepinput) V $ C(z) = G(z).G_{ZOH}G_1(z)E(z) = G(z).G_{ZOH}.G_1(z)(R(z) - C(z)) \Rightarrow C(z) = (R(z)-C(z)) $ C(z) = (z-1)^2/(z-1) $ \Rightarrow C(z) = \frac{z^2 - 1}{z - 1} = 1 +(z-1) + (z-1)^2 +.... \Rightarrow C(kT)=1 $ Pole zeros cancellation is ideal to bring the system to steady state: It will be hard to implement practically. Let's use another way. A block diagram showcasing the system. $ G(z)→(Z.O.H)× plant C(z) R(z) = M(z) = G_c(z).G(z) 1+G_c(z).G(z) = \frac{ 1 }{ G(z) } \frac { M(z) }{ 1-M(z) } \Rightarrow G_c(z) = \frac{1}{G(z)} \frac {M(z)}{1-M(z)} $ - Writing: E(z) = R(z) - C(z) = R(z)[1-M(z)] ⇒ E(z) = R(z)[1-M(z)] $ With the input: R(z) = \frac{A(z)}{(1-z^{-1})^N} N: positive integer. $ With A(z) polynomial in z^{-1} with no zeros at z=1 For unit step: R(z) = 1/(1-z^{-1}) ⇒ A(z) = 1; N =1 Unit Ramp (t): R(z) = (T.z^{-1})/(1−z−1)2 ⇒ A(z) = T.z¯¹ ; N = 2 Unit parabolic (t^2): R(z) = (T^2z^{-1}(1+z^{-¹}))/(1-z^{-1})^3 ⇒ A(z) = T^2z^{-1}(1+z^{-¹}); N = 3 ### 3.10 Digital Controller Design Design is the process of introducing suitable digital compensators into the sampled-data control system to achieve desired performance specifications ### 3.10.1 Compensation by Digital Controllers a) Original (uncompensated) system: A block diagram of a sampled-data system. Transfer function: C(z)/R(z) = G(z)/(1+GH(z)) b) System with digital controller (compensator): A block diagram of a closed-loop sampled-data system. Transfer function: C(z)/R(z) = D(z)G(z) / (1+D(z)GH(z)) c) Inner Loop Digital Compensation A block diagram of a closed-loop system with an inner loop digital compensator. Transfer function: $ \frac{C(z)}{R(z)} = \frac{Z^{-1}[\frac{G_1G_2R}{1+G_1G_2H_1}]}{1+D(z)Z^{-1}[\frac{G_1G_2}{1+G_1G_2H_1}]} $ Digital compensator D(z) is employed in the inner loop of the feedback system. Design goals - To decrease the steady-state tracking errors - To improve the system stability - To improve the system transient response and make it robust to parameter variations 1) To Decrease Steady-State Tracking Errors A block diagram of a closed-loop system. $ G(z) = \frac {1-e^{-T} }{z- e^{-T}} $ - Type 0 system, with e_{ss} = 0.5 for unit step input, and e_{ss} = ∞ for unit ramp input With a digital compensator: D(z) = K_1 + K_2 (z^{-1})/(z-1) ⇒ D(z)G(z) = (K_1 + K_2 (z^{-1})/(z-1)) (1- e^{-T})/(z - e^{-T}) - Type 1 system, with gain K_de = K_1, with e_{ss} = 0 for unit step input, and e_{ss} = T/K_1 for unit ramp 2) To Improve System Stability Stability is often characterized by the locations of the closed-loop poles and stability margin( gain margin and phase margin) 3) To Improve System Transient Response - Maximum overshoot ; Settling time; Rise time, peak time. 4) For Better Disturbance Rejection A block diagram of a closed loop system with disturbance input, F(s). Due to disturbance By choosing the compensator D(z)=K with a large K, the effect of disturbance on the system output can be significantly reduced without affecting the tracking performance. ### 3.10.2 Digital Controller Design using Root Locus 1) S-Plane Specifications $ H(s) = \frac{ ω_n^2 }{ s^2 + 2ζω_ns } $ A graph of the root locus of the system. - has two poles: p1,2 =-σ±jω_n With: σ=ζω_n and ω_n = √1-ζ^2 ω_n - Damping ratio: ζ and θ = tan^{-1}(√1-ζ^2/ζ) - Natural frequency: ω_n - Settling time (5%): t_s ≅ 3/(ζω_n) ≅ ζπ/√(1-ζ^2) - Maximum overshoot: M = e^(-ζπ/√(1-ζ^2)) 2) z-Plane Specifications Procedures for Deriving z-Plane Specifications - Given a set of continuous-time specifications (maximum overshoot, rise time, settling time) - Determine the desired (ζ and ω_n - From the z-grids, find the locations of the dominant poles of the corresponding discrete system: $ Z_1,2 = e^{s_1,2T}= e^{(-ζω_n±jω_n√1-ζ^2)T}=e^{-ζω_nT}e^{±joT√1-ζ^2}=r.e^{±jθ} $ Where: r = e^(-ζω_nT) and θ = Tω_n√(1-ζ^2) A graph of the z-grid. Example: G(z) = ( 0.0484(z